Analysis of Factors Affecting the Financial Health of General Insurance Companies and Life Insurance Companies in Indonesia for the Period of 2013 – 2021 - Beaty, Zuly Puspita; Suardi, Lenny (Riviera Publishing, 2025)
Financial health is an important factor for insurance companies. This study aims to analyze the factors that affect the level of financial health of general insurance companies and life insurance companies in Indonesia. This study uses logistic regression analysis and survival analysis. The results of the analysis show that the return on assets has a negative influence on the non-fulfillment of the financial health of life insurance companies or the general public. Meanwhile, the claim ratio has a positive influence on the financial health of the insurance company. In life insurance companies, the placement of insurance in bond instruments or debt securities has a negative effect on the non-fulfillment of the financial health condition of the insurance company. The results obtained between logistics regression and survival analysis for life insurance companies are not much different. However, the results of the survival analysis produced for general insurance companies are biased. This study contributes to understanding insolvency risks in emerging-market insurance systems using dual-model analysis, offering practical implications for regulators and practitioners in developing economies with limited policyholder protection mechanisms.